Identification Of Types Companion Plants for Aren Plants (Arenga Pinnata Merr) and Agroforestry Patterns of Community Forests Area - Darmadi Erwin Harahap; Retna Astuti Kuswardani; Tumpal H.S. Siregar; Muhammad Darwis (Jurnal Penelitian Pendidikan IPA, 2023)
The aren palm plant is a multi-purpose plant, where almost all parts of this plant can be utilized. One of them is nira water which can be used as sugar. his study aims to identify types of companion plants for sugar palm and agroforestry patterns used in community forests in South Tapanuli Regency. The research method used in this study was a field survey in three villages that have community forests. The results showed that there were 17 types of companion plants growing around the sugar palm plants. The pattern of the agroforestry system that occurs in the forests of South Tapanuli Regency is natural. The results showed that coffee plants were dominated in Simaninggir and Bulu Mario villages, while in Aek Nabara village it was dominated by zalacca plants